2021
DOI: 10.1093/ofid/ofab621
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Changes After Switch From TDF to TAF in the OPERA Cohort: LDL Cholesterol and Triglycerides

Abstract: Background Increases in lipids have been observed in people living with HIV (PLWH) switching from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF). We assessed changes in low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG) following a switch from TDF to TAF. Methods Adults with ≥1 lipid measure before and after switch from TDF-to-TAF were identified in the OPERA® cohort. Multivariable linear r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…On the other hand, HIV-infected patients have to use lifelong antiretroviral drugs that have to be optimized to reduce long-term metabolic impact. Regarding antiretroviral therapy (ART), there are many data in the literature on dyslipidemia associated with a switch from TDF to TAF in treatment-experienced HIV patients [ 5 , 6 , 7 , 8 ]. In particular, in a recent real-world study on 6423 HIV-experienced patients, Brunet et al showed a development of dyslipidemia associated however to an underutilization of statin after switching from TDF to TAF [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, HIV-infected patients have to use lifelong antiretroviral drugs that have to be optimized to reduce long-term metabolic impact. Regarding antiretroviral therapy (ART), there are many data in the literature on dyslipidemia associated with a switch from TDF to TAF in treatment-experienced HIV patients [ 5 , 6 , 7 , 8 ]. In particular, in a recent real-world study on 6423 HIV-experienced patients, Brunet et al showed a development of dyslipidemia associated however to an underutilization of statin after switching from TDF to TAF [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the introduction of tenofovir alafenamide (TAF) has deeply modified the choice of the backbone, allowing the prevention of bone and renal toxicity related to previous formulations of tenofovir disoproxil fumarate (TDF) [ 1 , 2 , 3 , 4 ]. However, some evidence suggests that the switch from TDF to TAF could be associated with a higher incidence of dyslipidemia [ 5 , 6 , 7 , 8 ]; this could be due to a “statin-like” effect of TDF, as clinical trials and real-life studies suggest [ 9 ]. In some publications, dyslipidemia, after this switch, was associated with higher cardiovascular risk [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism is unclear, an association between TDF and a decrease in lipid levels has been reported in several studies (23)(24)(25). In a study conducted by Malloon et al (26) examining the lipid profile of patients who were switched from TDF to TAF, an increase in LDL and triglyceride levels was observed after 9-16 months. In our study, an increase in total cholesterol, LDL and triglyceride levels and a decrease in HDL levels were found in patients whose lipid profile was monitored, but no statistically significant difference was found (p>0.05).…”
Section: Discussionmentioning
confidence: 96%
“…We report a high prevalence of MetS and central obesity among females irrespective of HIV status in an urban population in Zambia and Zimbabwe. The rollout of DTG and tenofovir alafenamide, which have been linked to weight increases and worsening lipid profiles among PLWH, could further exacerbate the burden of metabolic complications in the region [ 29 , 30 , 31 ]. As approximately 90% of PLWH in our study initiated a DTG‐containing regimen, the prospective monitoring of metabolic parameters in our study will improve our knowledge on the impact of contemporary ART on associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%